Butterfly (Lepidoptera: Papilionoidea) fauna of Kangkawat Research Station, Imbak Canyon Conservation Area, Sabah, Malaysia - Norradihah Ismail; Aqilah Awg Abdul Rahman; Maryati Mohamed; Razy Japir; Gao Le; Fiffy Hanisdah Saikim (2020)
Forty-three species of butterflies from 36 genera and six families are reported for Kangkawat Research Station, Imbak Canyon Conservation Area (ICCA). This accounts for 4.6 percent of the 944 species reported in Borneo. Compared to studies from other localities in ICCA, the butterfly fauna in Kangkawat Research Station is diverse and evenly distributed with a Shannon’s index of Diversity (H’) value of 3.636 and Simpson’s index of Species Evenness (E1/D) value of 0.776.The most dominant family is Nymphalidae with 27 species recorded followed by Lycaenidae with 11 species. Seven species are new records for ICCA: Eurema blanda, Mycalesis dohertyi, Nacaduba berenice, Arhopala aedias agnis, Arhopala agesias, Drupadia cineas and Taractrocera ardonia. Three species: Mycalesis kina, Acytolepis ripte and Drupadia cineas, which are endemic to Borneo are also recorded here. The presence of the butterfly species of high conservation value highlights Kangkawat Research Station as an important area for conservation of these species.